Imaging Violence in Schizophrenia: A Systematic Review and Critical Discussion of the MRI Literature - Fjellvang, Maria; Grøning, Linda; Haukvik, Unn K. (Frontiers in Psychiatry, 2018)
Background: Persons with schizophrenia have a small but significant increase in risk of violence, which remains after controlling for known environmental risk factors. In vivo MRI-studies may point toward the biological underpinnings of psychotic violence, and neuroimaging has increasingly been used in forensic and legal settings despite unclear relevance. Objectives: 1. To present the first systematic review, following standardized guidelines, of MRI studies of violence with schizophrenia. 2. To critically discuss the promises and pitfalls of using this literature to understand violence in schizophrenia in clinical, forensic, and legal settings. Methods: Following the PRISMA guidelines and literature searches until January 2018, we found 21 original studies that fulfilled the inclusion criteria: 1) Studies of persons with schizophrenia, 2) a history of violence or aggressive behavior, 3) the use of one or more MRI-modalities (sMRI, DTI, fMRI). Results: The most consistent findings from the structural studies were reduced volumes of the hippocampus and the frontal lobe (in particular the orbitofrontal and anterior cingulate cortex) in schizophrenia patients with a history of violence or higher aggression scores. The functional studies mainly showed differences and aggression correlates in the frontal lobe and amygdala. However, the studies were methodologically heterogeneous, with four particular areas of concern: different definitions of violence, region of interest versus whole-brain studies, small subject samples, and group comparisons in a heterogeneous diagnostic category (schizophrenia). Conclusion: The literature reports subtle, but inconsistent group level differences in brain structure and function associated with violence and aggression with schizophrenia, in particular in areas involved in the formation of psychosis symptoms and affective regulation. Due to methodological challenges the results should be interpreted with caution. In order to come closer to the neurobiological underpinnings of violence in schizophrenia future studies could: (1) address the neurobiological differences of premeditated and reactive violence, (2) use RDoC criteria, for example, or other symptom-based systems to categorize psychosis patients, (3) increase subject cohorts and apply new data driven methods. In this perspective, MRI-studies of violence in schizophrenia have the potential to inform clinical violence prediction and legal evaluations in the future.